Inclusion of gender and intersectionality in climate change, land, and food policies: The case of Colombia - Howland, Fanny; Buritica, Alexander; Lopera, Diana Carolina; Blanco, Maria; Pierce, Deborah (2023)
This study aims to evaluate the incorporation of gender and intersectionality (G&I) in Colombian policies pertaining to climate, land, and food. It is conducted within the framework of the CGIAR Initiative on National Policies and Strategies.